Adaptive and iterative signal processing in communications - Choi, Jinho (Cambridge University Press, 2006)
Using examples from practical transceiver design, this book describes the fundamental theory and practical aspects of using ASP, and ISP, to improve the performance of receivers in communication systems. Suitable for graduate students and researchers in electrical engineering, and practitioners in the telecommunications industry.
Keywords: Adaptive signal processing.; elektronické knihy; electronic books